Tracing the Intellectual Landscape of Corporate Taxation in Recent Scholarship - Rahayu, Puspita; Andriani, Sri (Maliki Interdisciplinary Journal, 2025)
This study aims to map the structure and development of corporate taxation research using bibliometric analysis to identify trending topics and reveal potential gaps for future inquiry. Using the Scopus database, 342 articles from 2019 to 2023 were analyzed with VOSviewer software to construct visual co-occurrence maps of keywords. The analysis revealed five main clusters, namely tax rate and policy, tax avoidance and planning strategies, corporate governance, firm value, and corporate tax compliance driven by social responsibility. These findings confirm the multidimensional nature of corporate taxation studies, indicating a strong interplay between fiscal policies, ethical considerations, and firm behavior. The results imply that future research should adopt an integrative approach that includes economic, legal, and social perspectives to address the complexity of taxation. The novelty of this research lies in its comprehensive bibliometric mapping, offering a systematic overview that can guide scholars in developing focused, impactful studies and assist policymakers in understanding global research trends in corporate taxation.